Braden Scale and Norton in Predicting Risk of Pressure Sores in ICU Room - Maria Walburga Bhoki; Mardiyono Mardiyono; Sarkum Sarkum (Jurnal Riset Kesehatan, 2014)
This study aimed to compare the effectiveness of the Braden Scale and Norton Scale in predicting the risk of pressure sores in patients in ICU. This research was a prospective observational analytic study, with 42 respondents who met the inclusion criteria. Testing the predictive validity of the Braden scale and the Norton Scale was to calculate sensitivity, specificity, FN,FP, and area under the curve.Testing thereliability used Cronbach Alpha(α). The Braden scale has a good predictive validity by the cut of 15 point,  a valuable sensitivity at 86.67, specificity at 70.37, FP at 29.63, FN at 13.33, area under the curve at 0.808. The Norton Scale has predictive validity bythe cut of 14 point, a valueable sensitivity at 80, specificity at 66.67, FP at 33.33, FNat 20, area under thecurve at0.707.Braden Scale reliability test results of 0.818, 0.707 Norton scale. The Braden scale was more effective to predict the risk of pressure sores in critical patients.